Involuntary mental imagery is influenced by visual salience - Alexander J. Cook; Dennis Lambert; Mark W. Geisler; Ezequiel Morsella (Acta Psychologica, 2025)
The attention bottleneck theory suggests that object recognition is limited to one item at a time. A default attentional set may guide attention to unique items when no specific goal is present. The Reflexive Imagery Task (RIT) examines involuntary mental imagery by asking participants not to think of the name of a centrally presented object. Surprisingly, mental imagery occurs on many trials. This study investigates whether similar effects happen when multiple objects appear near the periphery of vision. RIT effects were observed for these objects, with the names of salient singletons reported more often. Imagery is reported more for objects with a heterogeneous feature than homogeneous ones. However, a unique object defined by two features did not yield the same effect. When the task is to ignore all objects, salient objects are more likely to receive initial cognitive processing. These findings contribute to understanding involuntary mental imagery and attentional capture.